Waldemar Westergaard collection - Westergaard, Waldemar, 1882-1963.
Transcripts of selected documents from the Rigsarkivet (Danish State Archives), Kongelige Bibliotek (Royal Library of Denmark), and Raadstuearkivet Copenhagen (Municipal Archives of Copenhagen), and from the Bancroft Library of the University of California at Berkeley pertaining to the Danish West Indies (later the United States Virgin Islands), 1692-1806. Relates chiefly to the Vestindisk-Guineiske kompagni (Danish West Indies-Guinea Company) established to colonize, maintain commerce primarily between the Danish West Indies and Guinea, and manage the Danish settlements. Also selections on microfilm of documents in the Rigsarkivet and the Public Record Office, London, relating to northern European international relations in the sixteenth to eighteenth centuries. Focuses primarily on Denmark, England, France, Germany, and Russia.
Microfilm edition available
Microfilm and transcripts of originals in Danish, English, and U.S. repositories.
Denmark: Rigsarkivet, Copenhagen
Great Britain: Public Record Office, London
Denmark: Kongelige Bibliotek, Copenhagen
Denmark: Raadstuearkivet, Copenhagen
Keywords: Vestindisk-Guineiske kompagni; Caribbean Area -- History -- To 1810.; Danish West Indies -- Commerce; Danish West Indies -- Commerce -- Guinea; Danish West Indies -- History; Denmark -- Colonies -- America; Denmark -- Foreign relations -- 16th century; Denmark -- Foreign relations -- 17th century; Denmark -- Foreign relations -- 18th century; England -- Foreign relations -- 16th century; England -- Foreign relations -- 17th century; England -- Foreign relations -- 18th century; Europe, Northern -- Foreign relations -- 16th century; Europe, Northern -- Foreign relations -- 17th century; Europe, Northern -- Foreign relations -- 18th century; France -- Foreign relations -- 16th century; France -- Foreign relations -- 17th century; France -- Foreign relations -- 18th century; Germany -- Foreign relations -- 16th century; Germany -- Foreign relations -- 17th century; Germany -- Foreign relations -- 18th century; Guinea -- Commerce -- Danish West Indies; Guinea -- Commerce -- United States Virgin Islands; Russia -- Foreign relations -- 16th century; Russia -- Foreign relations -- 17th century; Russia -- Foreign relations -- 18th century; United States Virgin Islands -- Commerce; United States Virgin Islands -- Commerce -- Guinea; United States Virgin Islands -- History; Historians